2015
DOI: 10.1038/srep08662
|View full text |Cite
|
Sign up to set email alerts
|

Selective spatial attention modulates bottom-up informational masking of speech

Abstract: To hear out a conversation against other talkers listeners overcome energetic and informational masking. Largely attributed to top-down processes, information masking has also been demonstrated using unintelligible speech and amplitude-modulated maskers suggesting bottom-up processes. We examined the role of speech-like amplitude modulations in information masking using a spatial masking release paradigm. Separating a target talker from two masker talkers produced a 20 dB improvement in speech reception thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…Earlier research indicates that selective attention to one speech stream does not mean that humans can completely ignore unattended sounds. Acoustic and linguistic properties of unattended speech can influence attended speech processing, known as informational masking 48,49 or attentional leakage 50 . However, in all these cases, the interference from unattended acoustic and linguistic cues is reduced relative to the contribution of attended speech.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research indicates that selective attention to one speech stream does not mean that humans can completely ignore unattended sounds. Acoustic and linguistic properties of unattended speech can influence attended speech processing, known as informational masking 48,49 or attentional leakage 50 . However, in all these cases, the interference from unattended acoustic and linguistic cues is reduced relative to the contribution of attended speech.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to EM, IM has been a challenge to define and is often conceptualized as the interference from noise once EM is accounted for (Cooke et al, 2008). In other words, the definition of IM is primarily a "classification by exclusion" (Carlile & Corkhill, 2015). This study does not suggest that the lexical (i.e., two-talker babble) and nonlexical (i.e., pink noise) distinction is synonymous with the IM and EM distinction, as IM does not mandate the presence of lexical interferences.…”
Section: Potential Implications On the Distinction Of Energetic Maskementioning
confidence: 99%
“…Previous research even suggested that selective spatial attention modulated bottom-up informational masking of speech when only the auditory modality was presented 5 . In our study, we further investigate the relationships between the bottom-up mechanisms of multisensory integration and the top-down attentional processes.…”
Section: Discussionmentioning
confidence: 99%